Similarities and Differences Between HFmrEF and HFpEF - Li, Peixin; Zhao, Hengli; Zhang, Jianyu; Ning, Yunshan; Tu, Yan; Xu, Dingli; Zeng, Qingchun (Frontiers in Cardiovascular Medicine, 2021)
The new guidelines classify heart failure (HF) into three subgroups based on the ejection fraction (EF): HF with reduced EF (HFrEF), HF with mid-range EF (HFmrEF), and HF with preserved EF (HFpEF). The new guidelines regarding the declaration of HFmrEF as a unique phenotype have achieved the goal of stimulating research on the basic characteristics, pathophysiology, and treatment of HF patients with a left ventricular EF of 40–49%. Patients with HFmrEF have more often been described as an intermediate population between HFrEF and HFpEF patients; however, with regard to etiology and clinical indicators, they are more similar to the HFrEF population. Concerning clinical prognosis, they are closer to HFpEF because both populations have a good prognosis and quality of life. Meanwhile, growing evidence indicates that HFmrEF and HFpEF show heterogeneity in presentation and pathophysiology, and the emergence of this heterogeneity often plays a crucial role in the prognosis and treatment of the disease. To date, the exact mechanisms and effective treatment strategies of HFmrEF and HFpEF are still poorly understood, but some of the current evidence, from observational studies and post-hoc analyses of randomized controlled trials, have shown that patients with HFmrEF may benefit more from HFrEF treatment strategies, such as beta-blockers, angiotensin-converting enzyme inhibitors, angiotensin receptor blockers, mineralocorticoid receptor antagonists, and sacubitril/valsartan. This review summarizes available data from current clinical practice and mechanistic studies in terms of epidemiology, etiology, clinical indicators, mechanisms, and treatments to discuss the potential association between HFmrEF and HFpEF patients.